MOSAIC DISEASE OF MAIZE CAUSED BY SUGARCANE MOSAIC POTYVIRUS IN SULAWESI - Wakmana, W.; Kontong, M.S.; Muis, A.; Persley, D.M.; Teakle, D.S. (Indonesian Agency for Agricultural Research and Development - MOA, 2001)
Mosaic disease of maize and grasses is commonly found in Sulawesi. The symptoms resemble the common mosaic symptoms of virus infection, but the pathogen has not been identified. The objective of this study was to identify the causal agent of the mosaic disease of maize and grasses in Sulawesi. Transmissions of the virus were studied by mechanical inoculation and the insect vector aphid. Serological study was done by using enzyme linked immunosorbent assay (ELISA). Results of mechanical inoculation showed that the disease was caused by a virus which was transmitted from diseased maize and grasses to healthy sweet corn seedlings. The disease was also transmitted by aphid (Rhopalosiphum maidis). Serological study indicated that the virus was closely related to the sugarcane mosaic virus (SCMV). Based on these results, it can be concluded that the maize and grass mosaic disease was caused by SCMV.